Accumulation of senescence observed in spinocerebellar ataxia type 7 mouse model. - William Miller; Charles Lewis Humphrey Pruett; William Stone; Cindy Eide; Megan Riddle; Courtney Popp; Matthew Yousefzadeh; Christopher Lees; Davis Seelig; Elizabeth Thompson; Harry Orr; Laura Niedernhofer; et al. (PLoS ONE, 2022)
Spinocerebellar ataxia type 7 (SCA7) is a neurodegenerative disease caused by a trinucleotide CAG repeat. SCA7 predominantly causes a loss of photoreceptors in the retina and Purkinje cells of the cerebellum. Severe infantile-onset SCA7 also causes renal and cardiac irregularities. Previous reports have shown that SCA7 results in increased susceptibility to DNA damage. Since DNA damage can lead to accumulation of senescent cells, we hypothesized that SCA7 causes an accumulation of senescent cells over the course of disease. A 140-CAG repeat SCA7 mouse model was evaluated for signs of disease-specific involvement in the kidney, heart, and cerebellum, tissues that are commonly affected in the infantile form. We found evidence of significant renal abnormality that coincided with an accumulation of senescent cells in the kidneys of SCA7140Q/5Q mice, based on histology findings in addition to RT-qPCR for the cell cycle inhibitors p16Ink4a and p21Cip1 and senescence-associated ß-galactosidase (SA-ßgal) staining, respectively. The Purkinje layer in the cerebellum of SCA7140Q/5Q mice also displayed SA-ßgal+ cells. These novel findings offer evidence that senescent cells accumulate in affected tissues and may possibly contribute to SCA7's specific phenotype.